Odd-even effects in aryl-substituted alkanethiolate SAMs: nonsymmetrical attachment of aryl unit and its impact on the SAM structure - Azzam, Waleed; Subaihi, Abdu; Rohwerder, Michael; Bashir, Asif; Terfort, Andreas; Zharnikov, Michael (Physical chemistry, chemical physics, 2024)
Due to non-symmetric attachment of the anthracene unit to the alkanethiolate linker, the respective monolayers on Au(111) exhibit low extent of the odd-even effects and distinct polymorphism, showing, at the same time, high structural order. - , - - Aryl-substituted alkanethiolate (AT) self-assembled monolayers (SAMs) exhibit typically so-called odd-even effects, - viz. - systematic variations in the film structure, packing density, and molecular inclination depending on the parity of the number of the methylene units in the alkyl linker, - n - . As an exception to this rule, ATs carrying an anthracen-2-yl group (Ant- - n - ) as tail group were reported to have different behavior due the non-symmetric attachment of the anthracene unit to the AT linker, providing additional degree of freedom for the molecular organization and allowing for partial compensation of the odd-even effects. In this context, the structure of SAMs formed by adsorption of anthracene-substituted ATs (Ant- - n - ; - n - = 1-6) at room temperature on Au(111) substrate was investigated by high-resolution scanning tunnelling microscopy (STM). Most of these SAMs exhibit a coexistence of two different ordered phases, some of which are common for either - n - = odd or - n - = even while other vary over the series, showing a broad variety of different structures. The average packing density of the Ant- - n - SAMs, derived from the analysis of the STM data, varies by 7.5-10% depending on the parity of - n - , being, as expected, higher for - n - = odd. The respective extent of the odd-even effects is noticeably lower than that usually observed for other aryl-substituted monolayers (∼25%), which goes in line with the previous findings and emphasizes the impact of the non-symmetric attachment of the aromatic unit.
Gesehen am 05.08.2024